Optimasi Pola Operasi Waduk Pelaparado Di Kabupaten Bima, Propinsi NTB - Hilmi, Moh.; Masrevaniah, Aniek; Soetopo, Widandi (Fakultas Teknik, Universitas Brawijaya, 2012)
In utilizing reservoir capacity, it should be notice that water quantity is highly limited, therefore water usage should be as efficient as possible. For this matter, it is necessary to optimize reservoir operation that related with reservoir water usage in order to fulfill all predetermined needs. One means to improve water utilization is by using optimization technique with Dynamic Program. Dynamic Program could imitate system behavior and therefore could be use to make decision from set of related decisions. This is in accord with reservoir optimization problem since reservoir operational pattern is highly dependent with time thus it should be resolve in gradual way.In this study, optimization process is divided into 3 stages, in each stage there would be some water volume allocated. Variables that connecting each stages is reservoir capacity alteration before or after a stage with grid 100 thousand m3, other than this optimization also done using alternative method by altering comparison percentage in cultivating area between rice plant (paddy) and dry season crops in 2nd cultivating season. During optimization its decision variables is the amount of reservoir water volume that being used to produce optimum profit in agricultural production. Optimization result is a back trace therefore we could gain optimal path in the form of reservoir capacity allocation that could raise maximum profit in agriculture production. Maximum profit that gained in alternative option for comparison of cultivating area between rice plant in 10% and dry season crop in 90% for second cultivating season with value of Rp. 57.755.117.590,-. Water volume that should be given toward each periods would based on water availability and needs, therefore maximum gain is cultivation season for 31.300 thousand m3, second cultivating season for 22.300 thousand m3, and third cultivating season for 15.900 thousand m3. Area resulted from optimization is paddy I=3.806 Ha, paddy II=380 Ha,dry-crop II=3.422 Ha, and dry-crop III=2.327 Ha. Improvement in profit of agriculture production after optimization compared with before optimization are Rp. 57.755.117.590,- - Rp. 56.289.203.000,- = Rp. 1.465.914.590,-.Keywords: reservoir, optimization, dynamic